2014
DOI: 10.9790/3008-09233437
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Attitude and Perception of Pharmacovigilance and Adverse Drug Reaction (ADR) Reporting among the Pharmacy Students in South India

Abstract: The Study entitled "Assessment of Knowledge, Attitude and perception of Pharmacovigilance and Adverse Drug Reaction (ADR) Reporting among the Pharmacy Students in South India" was designed to assess the awareness of Pharmacovigilance and ADR reporting, and to evaluate the impact of an educational intervention. A validated (pilot study) self administered (KAP) Knowledge, attitude, perception survey questionnaire was used in the study. This prospective knowledge attitude practice (KAP) questionnaire study, of 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 24 publications
3
20
0
Order By: Relevance
“…11,12 A similar study in Andhra Pradesh revealed almost equal participation of male (49.3%) and female (50.7%) responders. 13 Present study reported that 76% of the total study population were of middle age between 25 years to 50 years old. Similar observations were reported in the studies in Mumbai and Nagpur where the mean age of the respondents was 26 years.…”
Section: Discussionmentioning
confidence: 68%
“…11,12 A similar study in Andhra Pradesh revealed almost equal participation of male (49.3%) and female (50.7%) responders. 13 Present study reported that 76% of the total study population were of middle age between 25 years to 50 years old. Similar observations were reported in the studies in Mumbai and Nagpur where the mean age of the respondents was 26 years.…”
Section: Discussionmentioning
confidence: 68%
“…The survey instrument was developed based on existing literature on medication safety [14,[17][18][19]. Modification was made to suit the local situation such as we modified the questions to test the respondents' knowledge towards the Malaysian ADR reporting system.…”
Section: Questionnaires Developmentmentioning
confidence: 99%
“…A structured questionnaire was designed after minor modifications. 12,13 The KAP questionnaire consisted of 20 questions about pharmacovigilance. Out of which, 11 questions were related to knowledge, 05 questions were related to attitude, 04 questions were related to perception.…”
Section: Methodsmentioning
confidence: 99%